New coloured coatings to enhance silica sand absorbance for direct particle solar receiver applications. (June 2020) - Gimeno-Furio, A.; Hernandez, L.; Martinez-Cuenca, R.; Mondragón, R.; Vela, A.; Cabedo, L.; Barreneche, C.; Iacob, M.
Abstract: New systems using solid particles for solar energy capturing, heat transfer and thermal energy storage have been proposed and analysed in direct particle solar receivers. In this work, black coloured silica sand was investigated as a possible solid particle for such combined systems. Two different methods based on a carbon coating approach were implemented to black colour the initial material to improve their solar absorption characteristics. The morphology of the raw and coloured sands was analysed by scanning electron microscopy (SEM), particle size characterisation and porosity measurements. The coating of the black-coloured silica sands was evaluated by thermogravimetry. Solar absorption was characterised in a double-beam UV-VIS spectrophotometer combined with an integrating sphere, and with enhancements of approximately 100%, found for both coloured sands. The thermal storage and heat transfer capabilities of the initial and coated sands were measured at different temperatures. Some improvements in the specific heat capacity and reductions in thermal conductivity due to porosity changes were observed. Highlights: Sand was black coloured through two different methods. Coloured sands were evaluated as candidates for direct particle solar receivers. SEM and TGA were used to study coating morphology and its stability with temperature. The absorption is highly improved for the both black sands compared to the raw sand. Improvements in Cp and reductions in thermal conductivity were observed.